Kierkegaard's Journals and Notebooks, Volume 1 : Journals AA-DD - Kierkegaard, Søren, 1813-1855 (Book collections on Project MUSE., 2016)
The first of an eleven-volume series produced by Copenhagen's Søren Kierkegaard Research Centre, this volume is the first English translation and commentary of Kierkegaard's journals based on up-to-date scholarship. It offers new insight into Kierkegaard's inner life. In addition to early drafts of his published works, the journals contain his thoughts on current events and philosophical and theological matters, notes on books he was reading, miscellaneous jottings, and ideas for future literary projects. Kierkegaard wrote his journals in a two-column format, one for his initial entries and the second for the marginal comments he added later. The new edition of the journals reproduces this format and contains photographs of original manuscript pages, as well as extensive scholarly commentary. Translated by leading experts on Kierkegaard, Journals and Notebooks will become the benchmark for all future Kierkegaard scholarship.